2022
DOI: 10.1371/journal.pone.0269595
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the importance of PLAUR in the progression and immune microenvironment of renal clear cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is a common type of kidney cancer with a high mortality rate, and the discovery of new therapeutic markers is essential to improve patient survival. The plasminogen activator urokinase receptor (PLAUR) plays key roles in tissue remodeling and extracellular matrix degradation, which contribute to invasion and metastasis, a major feature of tumor malignancy. The role of PLAUR in ccRCC pathology has not been deeply studied. In this study, we collected the mRNA expression da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For instance, the predictive biomarker ST3GAL5 has been linked to CD8 + T-cell depletion in ccRCC [ 21 ]. A poor prognosis for ccRCC can result from high PLAUR expression [ 22 ]. LGALS1 can predict probable immunological checkpoints and the effectiveness of anti-PD1 treatment in ccRCC patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the predictive biomarker ST3GAL5 has been linked to CD8 + T-cell depletion in ccRCC [ 21 ]. A poor prognosis for ccRCC can result from high PLAUR expression [ 22 ]. LGALS1 can predict probable immunological checkpoints and the effectiveness of anti-PD1 treatment in ccRCC patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the role of PLAUR in ccRCC remains unelucidated. Preliminary studies have found that PLAUR is significantly higher in ccRCC tissues, and the increased expression of PLAUR is tightly implicated in the poor prognosis of patient ( Wang et al, 2022a ; Wang et al, 2022b ). In the field of medicine, the search for effective therapeutic targets has always been a primary focus of scientists in treating various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the researchers suggest that an elevated expression of PLAUR is tightly linked to a poor prognosis in ccRCC. This gene not only serves as a crucial potential indicator for predicting macrophage infiltration and the immune microenvironment status, but also emerges as a promising target for ccRCC immunotherapy ( Wang et al, 2022b ). Based on these findings, we postulate that PLAUR can effectively serve as both a diagnostic and prognostic biomarker for ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Its ligand uPA catalyzes plasminogen to form plasminogen and produces a proteolytic cascade, which contributes to tissue remodeling and ECM decomposition, and creates favorable conditions for tumor invasion and metastasis 49 . One study reported that PLAUR was significantly overexpressed in renal clear cell carcinoma and the level of PLAUR and PLAUR methylation was significantly correlated with poor prognosis and participated in the progression of renal clear cell carcinoma 50 . Similarly, Zhang et al demonstrated that PLAUR can promote the growth and metastasis of gastric cancer and promote the loss of nesting apoptosis tolerance in gastric cancer cells by constructing the MKN45 gastric cancer mouse model and gastric cancer cell suspension anoikis model for 24 h 51 .…”
Section: Discussionmentioning
confidence: 99%